1996
DOI: 10.4141/cjss96-047
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of tillage and crop rotations on soil organic C and total N in a clay soil in southwestern Saskatchewan

Abstract: Soil organic matter contributes to the productivity and physical well-being of soils. An 11-yr study was conducted on a clay soil in the Brown soil zone in southwestern Saskatchewan to determine the influence of tillage and cropping frequency on soil organic C and total N content. Carbon and N behaved in a similar manner. Cropping frequency did not affect soil organic C or total N content, but soil C and N were greater under no-tillage (NT) than under mechanically tilled continuous wheat (Triticum aestivum L.)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
112
0
2

Year Published

2001
2001
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 186 publications
(121 citation statements)
references
References 2 publications
7
112
0
2
Order By: Relevance
“…1 for the F-W, F-W-W and W-Lent (N + P) rotations for the period 1967-1996(Campbell et al 2000a. In this paper we further tested the effectiveness of Eq.…”
Section: Estimating Soc Using Equationmentioning
confidence: 99%
See 3 more Smart Citations
“…1 for the F-W, F-W-W and W-Lent (N + P) rotations for the period 1967-1996(Campbell et al 2000a. In this paper we further tested the effectiveness of Eq.…”
Section: Estimating Soc Using Equationmentioning
confidence: 99%
“…The soil texture at this rotation site varies from loam to silty clay loam. Various workers have shown that there is a direct relationship between SOC and clay content (Campbell et al 1996). If the W-Lent treatment had consistently finer texture more uniformly distributed throughout the plots than the other treatments, it might have had a higher C content than the other rotations even in 1967.…”
Section: Estimating Soc Using Equationmentioning
confidence: 99%
See 2 more Smart Citations
“…No-tillage (or zero tillage) has been adopted by growers to improve the timeliness of operations and reduce costs, but other benefits include reduced erosion (Flower et al 2008) and improved soil carbon content (Campbell et al 1996;BlancoCanqui et al 2010). However, in sandy soils, retention of crop residues (stubble) can aggravate repellency (Harper and Gilkes 1994;Urbanek et al 2007;Blanco-Canqui 2011) because no-till concentrates organic matter and associated waxes in surface-soil layers.…”
Section: No-tillage and Stubble Retentionmentioning
confidence: 99%